Analisis Produktivitas Tenaga Kerja pada Bagian Produksi Menggunakan Metode Produktivitas Parsial di PT Prima Kemasindo - Habibah Habibah; Dene Herwanto (Jurnal Serambi Engineering, 2022)
PT Prima Kemasindo is a company that focuses on producing a variety of quality drinks, one of which is nata de coco or coconut juice. The machine used in producing this coconut juice drink is a filling machine. The amount of nata de coco production can be said to be unstable, this can be seen in the production results that there are decreases and increases every month. This study aims to analyze the level of labor productivity and what factors affect labor productivity at PT Prima Kemasindo. This study uses the partial productivity method to determine the level of labor productivity each month. The production output produced in January was 295604, in February it was 224714 and in March it was 279744. Labor productivity decreased in January by 95% (less than 100%), while February and March increased by 111% and 103%.